Metal–organic frameworks meet polymer brushes: enhanced crystalline film growth induced by macromolecular primers. (10th July 2017) - Rafti, Matías; Allegretto, Juan A.; Segovia, Gustavo M.; Tuninetti, Jimena S.; Giussi, Juan M.; Bindini, Elisa; Azzaroni, Omar
Abstract : We introduce tailor-made polymeric 3D primers, which produce a striking enhancement in MOF film growth compared to traditional primers. Abstract : We used poly-(3-sulfopropylmethacrylate) brushes as macromolecular 3D primers to promote heterogeneous nucleation and growth of archetypal ZIF-8 MOF thin films. The enhancement can be understood in terms of a high preconcentration of Zn 2+ ions in the polymer brush; this leads to a rapid increase of nucleation sites in the primer.